Determinants of entrepreneurial capability (EC) environment in ASEAN-05 economies: A log-linear stochastic frontier analysis - Munshi Naser Ibne Afzal; Shamim Ahmad Siddiqui; Susmita Dutta (Journal of Global Entrepreneurship Research, 2018)
The primary driver of this study is to find out key indicators of Entrepreneurial Capability milieu and test these components empirically in the Association with South East Asian Nations-05 economies. The purpose of this study is twofold. Firstly, it attempts to understand the determinants of Entrepreneurial Capability which identifies and endeavor commercial opportunities in the Association of South East Asian Nations 05 economies, namely Indonesia, Malaysia, the Philippines, Singapore and Thailand. Secondly, using the theory and determinants of entrepreneurial capability in general, this study empirically tests the efficiency imperative coefficients of variables that have an impact on entrepreneurial perceived capabilities. This research applies recent consistent estimation of log linear transformation stochastic frontier model to find out time-variant changes of variables in the panel sample. Data and variables have collected from Global Entrepreneurship Monitor - 2016 and World Competitiveness Yearbook - 2016 during the years 2010-2016. The results suggest that Entrepreneurship as a Good Career Choice and Perceived Opportunities are two significant variables which can improve and have a positive influence on entrepreneurial capability while Fear of failure rate has a negative impact on the efficiency of entrepreneurial capability in the Association of South East Asian Nations-05 countries. Other important variables such as Intellectual Property Rights, University Education and Knowledge Transfer rate have a positive stimulus to the entrepreneurial capability environment in these economies. The findings of this study are important contributions to the entrepreneurship literature and help policymakers to rethink entrepreneurial capability settings of the Association of South East Asian Nations-05 countries to pursue an innovation-driven region in future.
Keywords: O20; O30; O57; 650; ASEAN-05; Entrepreneurial capability; Panel study; Stochastic frontier analysis (SFA); Fixed effect model; Entrepreneurial environment